FICTIONAL DOMINANTS OF VASYL’ RIABYI’S EARLY CREATIVE WORK ON THE BACKGROUND OF EXPERIMENTAL LYRICS OF THE END OF THE XX TH – THE BEGINNING OF THE XXI ST CENTURY - Hrytsiuk, M. S. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The fictional dominants of early works of Vasyl Riabyi are analysed in the context of experimental poetry in the article. It is well-proven that a genre variety, metaphysical harmony, archetypеs, verbal game are the dominant artistic receptions of early author`s works.